ANALISIS TENTANG PUTUSAN MAHKAMAH KONSTITUSI NOMOR 21/PUU-XIII/2014 DALAM PANDANGAN TEORI NEGARA HUKUM - Mia Siratni (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
Decision of the Constitutional Court Number: 21 / PUU-XII / 2014, April 28, 2015 has fulfilled a sense of justice for the wider community because of how painful it is to bear the status of the suspect without knowing what exactly the mistakes he made, presumably every citizen whose status is determined as a suspect in the case general criminal offenses are also entitled to seek justice through pretrial. Not only in the special criminal environment (corruption). Thus perhaps things like that the legal event intended by Satjipto Rahardjo as a legal breakthrough or prorakyat law (progressive law) or the term Mochtar Kusumaatmadja is a good law because it is in accordance with the development of living justice values and develop in society.